Synthesis and Structural Insight into the Bioactivity of Imines with 1,5-Dimethyl-2-Phenyl-1H-Pyrazol-3(2H)-One Structural Unit Derived from Phenolic Aldehydes - Muamer Dizdar; Anela Topčagić; Monia Avdić; Danijela Vidic; Milka Maksimović (Kemija u Industriji)
This study focuses on the synthesis, characterisation, and bioactivity evaluation of four imines derived from the condensation of 4-aminoantipyrine with different phenolic aldehydes: 3-hydroxybenzaldehyde, 4-hydroxybenzaldehyde, 3,4-dihydroxybenzaldehyde, and 4-hydroxy-3-methoxybenzaldehyde. These compounds were synthesised to explore their potential in various biological activities, including antioxidant, acetylcholinesterase (AChE) inhibitory, and antibacterial activities. Characterisation of these imines by IR, 1H and 13C NMR, HR-ESI-MS, and elemental analysis confirmed their proposed structures. The antioxidant activity of the synthesised compounds was assessed using five different methods, with the imine derived from 3,4-dihydroxybenzaldehyde displaying the highest antioxidant activity, attributed to its catechol arrangement of phenolic groups. Additionally, the AChE-inhibitory activity of these compounds was investigated, revealing that the degree of hydroxylation and the introduction of a methoxy group significantly influenced their inhibitory efficacy. Molecular docking studies highlighted the main interactions between the imines and AChE, identifying the most energetically favourable binding sites. Antibacterial testing against Staphylococcus aureus, methicillin-resistant Staphylococcus aureus, Pseudomonas aeruginosa, and Escherichia coli indicated that all compounds exhibited broad antibacterial activities. This comprehensive analysis demonstrates the significant potential of these synthesised imines as bioactive molecules, offering insights into how structural modifications can enhance their biological functions.